"I just didn't want to trust it at all": Atrial fibrillation patient's treatment experience of rivaroxaban and warfarin. Issue 3 (11th October 2021) - Sly, Dan; Husted, Margaret; McKeague, Lynn; Everington, Tamara
Abstract: Background: In the treatment of atrial fibrillation (AF), anticoagulant medications such as warfarin and rivaroxaban are commonly prescribed to reduce the risk of ischaemic strokes, and other thromboembolic events. Research has highlighted advantages and disadvantages of each of these medications, but there remains an absence of qualitative evidence regarding the lived experiences of AF patients. The present study helps address this gap and obtain a greater understanding of the patient experience and beliefs surrounding their anticoagulant medication. Method: Semi‐structured qualitative interviews with a purposive sample of 20 participants (10 warfarin, 10 rivaroxaban). Interviews were transcribed verbatim and thematically analysed. Results: Data analysis led to the generation of three key themes: positive perceptions of medication, distrust of alternatives, and inconsistencies in support experiences. Conclusions: Positive perceptions of one anticoagulant medication (ACM) and distrust of alternatives may influence patients' confidence in switching medications. This is potentially problematic where there is a lack of patient engagement in medication changes, as seen during the COVID pandemic. Gaps in patient understanding of anticoagulation, including lack of clarity around medications selection and misconceptions about treatment, were evident. By addressing these misconceptions, clinicians may be better positioned to support people with AF in self‐management of their ACM.